Hacia una ciberconstitución. El reto de la digitalización = Towards a cyberconstitution. The challenge of digitalization - de Celis Gutiérrez, Eduardo (Revista Jurídica de la Universidad de León, 2021)
Estudio que aborda la situación actual de la Constitución Española de 1978 en relación con el Ciberespacio. En primer término, se analizará la nueva realidad jurídica que plantean los nuevos derechos surgidos de las Nuevas Tecnologías, para concluir con el análisis de la conveniencia o no de reformar la Carta Magna para adaptar la a la Era Digital. The Spanish Constitution of 1978 and the new challenges in Cyberspace defies the Constitutional Law due to the emerging new digital fundamental rights. The need of a Constitutional Reform in terms of digitalization is one of the legal challenges Spanish Nation will face in the next years. Classic Individual Rights and Public Freedoms such as Freedom of Speech, Honour, Privacy and Civic Rights and Duties will share space with these new Digital Rights